PENGARUH PROMOSI SOCIAL MEDIA, KUALITAS LAYANAN, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA ES TEH INDONESIA - Tio Berkah Romadhoni (2022)
This research is quantitative research conducted to determine the effect of social media promotions, service quality, and product quality on consumer purchasing decisions. The objects in this study are all consumers of Es Teh Indonesia and are located in the DKI Jakarta area. This study collected a sample of 100 respondents who were filtered using a purposive sampling method. Data was collected by distributing questionnaires and using SmartPLS 3.0 software to analyze the data. The results of this study indicate that (1) social media promotion variables have a positive and significant effect on purchasing decisions, (2) service quality does not have a positive and not significant effect on purchasing decisions, and (3) product quality has a positive and significant influence on purchasing decisions purchase